Greenwor(l)ds Ecocritical Readings of Canadian Women's Poetry - Relke, Diana M. A. (University of Calgary Press, 1999)
Greenwor(l)ds rewrites the literary history of Canada from a feminist ecological perspective through a series of essays that examine the lives and work of nine women poets. Using insights from fields of knowledge as disparate as history and biology, physics and philosophy, psychoanalysis and communications studies, these essays reflect the transdisciplinary character of women's studies generally and feminist ecocriticism in particular.